Non-vitamin K Antagonist Oral Anticoagulants and Drug-Food Interactions: Implications for Clinical Practice and Potential Role of Probiotics and Prebiotics - Sánchez-Fuentes, Ana; Rivera-Caravaca, José Miguel; López-Gálvez, Raquel; Marín, Francisco; Roldán, Vanessa (Frontiers in Cardiovascular Medicine, 2022)
Non-vitamin K antagonist oral anticoagulants (NOACs) are a therapeutic option to prevent stroke in patients with atrial fibrillation (AF). In fact, NOACs have become the recommended choice by international clinical practice guidelines over vitamin K antagonists (VKA), because of their efficacy and safety profile, especially in newly initiated patients. The more predictable pharmacokinetic and pharmacodynamic profile of this family of drugs allows preventing anticoagulation drug monitoring. Furthermore, NOACs have significantly fewer drug and food interactions in comparison with VKAs. Despite this, there are no studies that compare the effects on the quality of anticoagulation of NOACs with the intake of potential interactions drugs of P-glycoprotein and cytochrome P450 (CYP). This review brings an overview of NOACs pharmacokinetics profile and their potential drug-food interactions. We also briefly discuss the potential role of prebiotics and probiotics in patients under therapy with NOACs.